The Effectiveness of Group Guidance Services Using Self-Management Techniques to Reduce the Addiction to the Use of Social Media - Yulisma Pauza; A. Muri Yusuf; Neviyarni Neviyarni (International Journal of Applied Counseling and Social Sciences, 2020)
The development of social media has positive and negative impacts on society, especially students. One effort to reduce addiction to the use of social media is a group guidance service using self-management techniques. This study aims to examine the effectiveness of group guidance services using self-management techniques to reduce addiction to the use of social media. This study uses a pseudo experimental from the Non-Equivalent Control Group. The population in this study was Bener Meriah High School students with a sample of 18 students. The sampling technique used was purposive sampling. The results showed that the average score of addicted social media users in the experimental group average pre-test score was 216.22 in the next high category, the average post-test score decreased to 191 and in the medium category. In the control group, Before group guidance services were provided, the pre-test score averaged 219.56 in the high category. Furthermore, after being given group guidance services without using self-management techniques, the average post-test score dropped to 199 in the high category. Based on the results of this study, it was concluded that group guidance services using effective self-management techniques to reduce student addiction to the use of social media.